Performance Assessment of Civil Servants (PNS) in the Sub-Section for Oversight Facilities of the DPRD Secretariat of Lahat Regency - Desi Mariani; Tri Rusilawati; Amaludin Amaludin (JURNAL ISIP VOICE : Jurnal Ilmu Sosial dan Ilmu Politik, 2023)
Work performance appraisal is a process of evaluating employee work results based on the work assigned to them. Performance appraisal is used as a basis for assessing the success and failure of a Civil Servant (PNS) in carrying out activities following predetermined targets to realize organizational goals. Assessment of civil servant work performance consists of elements of employee work objectives (SKP PNS) with a weight of 60% and also work behavior with a weight of 40%. The purpose of this study was to find out how performance appraisal works in assessing the work of civil servants and see whether the existing performance appraisal system is reliable, and can be used as a basis for performance appraisal and employee achievement development according to organizational goals, especially in the Supervision Facilitation Sub-Division of the DPRD Secretariat of Lahat Regency. The research method used in this study is a qualitative approach in which the research carried out is descriptive which describes the actual phenomena in the field. Data collection techniques are interviews, observations, and documents related to research. Data analysis techniques in this study were carried out qualitatively. This study uses indicators of the effectiveness of Cascio's performance evaluation, especially in covering relatedness, sensitivity, reliability, practicality, and acceptability. The results of this study are that the Employee Work Target instruments (SKP) and work behavior used as a whole have been effective when viewed from the perspective of relevance, sensitivity, reliability, acceptability, and practicality. However, the work behavior instrument still requires objectivity from the appraiser so that the assessment results are not based on the subjectivity of the appraiser himself.